Personal, Social and Emotional Development of Children - Barnes Peter (Blackwell/The Open University, 1998)
A detailed and thorough undergraduate-level introduction to the central concepts, theories, current issues and research evidence in developmental psychology. Introduction, Child Care and Attachment, Disturbing Behavior in Young Children, Growing Up in Families, Developmental Perspectives on Emotion, Developing a Sense of Self, Play and Self and the Social World, Growth and Change in Adolescence, Reading: Studying Relationships and Social Understanding, Acknowledgements, Name and Subject Index.